Decreased Intra- and Inter-Salience Network Functional Connectivity is Related to Trait Anxiety in Adolescents - Geng, Haiyang; Li, Xuebing; Chen, Jie; Li, Xinying; Gu, Ruolei (Frontiers in Behavioral Neuroscience, 2016)
Objective: Adolescence is a critical period for the vulnerability of anxiety. Imaging studies focusing on adolescents’ susceptibility to anxiety suggest that the different development trajectories between the limbic system and the executive control system may play important roles in this phenomenon. However, few studies have explored the brain basis of this susceptibility from the perspective of functional networks. The salience network（SN）consists of a series of key limbic and prefrontal regions that are engaged in the development of anxiety, such as the amygdala, anterior insula (AI) and dorsal anterior cingulate cortex (dACC). Intra- and inter- network connections in this system play essential roles in bottom-up attention and top-down regulation of anxiety, nevertheless, little is known about whether the SN-centered connections are associated with trait anxiety (i.e., susceptibility to anxiety) in adolescents. Method: Here, we applied resting-state functional magnetic resonance imaging (fMRI) to explore the relationship between intra- and inter- network functional connectivity (FC) of the SN and trait anxiety in adolescents using the amygdala, AI and dACC as the regions of interest (ROI). Results: We found that trait anxiety levels were inversely associated with both characteristic AI-dACC FC in the SN and distributed inter-network FC between the SN and multiple functional systems, which included the default mode network and the executive control network. Conclusions: Our results indicate that weaker intra- and inter- network FC of the SN was linked to higher trait anxiety among adolescents, and it may underlie altered salience processing and cognitive regulation.